Development of a upper-limb exoskeleton robot for refractory construction. (March 2018) - Yu, Ho; Choi, Il Seop; Han, Kyung-Lyong; Choi, Jae Yeon; Chung, Goobong; Suh, Jinho
Abstract: In this paper, a novel 7-DOF (degree-of-freedom) upper-limb robotic exoskeleton was developed for helping refractory construction operations in furnaces. The exoskeleton is the dual-arm type wearable robot that cooperates with human operators. Each arm includes Force/Torque (F/T) sensors to detect the human's motion, and the robot can handle a refractory of up to 50 kg. The exoskeleton robot generates not only high strength but also various 3-dimensional motions with the load, and it is highly suitable for the refractory construction operation. Highlights: The dual-arm robotic exoskeleton for refractory construction in steel manufacturing.